The Role Of Civic Education In The Formation Of A Democratic Society (Udin Sarifudin Winataputra's Perspective) - Tiar Hajunilato; Samsuri samsuri; Suyato suyato (Journal of Social Research, 2024)
This article has the aim of providing a theoretical review of the role of Citizenship Education in the formation of a democratic society through the views or perspective of Prof. Dr. Udin Sarifudin Winataputra, M.A., This research tries to build and obtain results from the theoretical and empirical foundations of Citizenship Education both among the public as well as students and teachers in the world of education, which aims to be able to develop a concept of the role of Citizenship Education in forming a democratic society. In this article, it can be concluded that Citizenship Education has three main roles or functions in the formation of a democratic society, namely developing civic intelligence, cultivating civic responsibility, and encouraging citizen participation both among the community and among education. The three functions or roles of civics education are also in line with the three components of civics education, namely citizenship knowledge, civic values and attitudes, and citizenship skills.